A lightweight method for maize seed defects identification based on Convolutional Block Attention Module - Li, Chao; Chen, Zhenyu; Jing, Weipeng; Wu, Xiaoqiang; Zhao, Yonghui (Frontiers in Plant Science, 2023)
Maize is widely cultivated and planted all over the world, which is one of the main food resources.Accurately identifying the defect of maize seeds is of great significance in both food safety and agricultural production. In recent years, methods based on deep learning have performed well in image processing, but their potential in the identification of maize seed defects has not been fully realized. Therefore, in this paper, a lightweight and effective network for maize seed defect identification is proposed. In the proposed network, the Convolutional Block Attention Module (CBAM) was integrated into the pretrained MobileNetv3 network for extracting important features in the channel and spatial domain. In this way, the network can be focused on useful feature information, and making it easier to converge. To verify the effectiveness of the proposed network, a total of 12784 images was collected, and 7 defect types were defined. Compared with other popular pretrained models, the proposed network converges with the least number of iterations and achieves the true positive rate is 93.14% and the false positive rate is 1.14%.